Study of sub-nyquist sampling and noise folding effect - Sugunthan, T. (Nanyang Technological University, 2020)
Sub-Nyquist sampling, sampling below Nyquist rate, was introduced to reduce the computational load and storage space caused when adhering to the Nyquist-Shannon sampling theorem. Studies over the years resulted in different schemes to achieve sub-Nyquist sampling. However, it has a major drawback of noise folding effect (NFE), which results to the degradation of the signal quality. Till now there is no actual implementation that successfully minimizes the NFE in any of the sub-Nyquist sampling schemes. In this project, modulated wideband converter (MWC), a popular sub-Nyquist sampling scheme, was chosen to examine the NFE. The detailed study was conducted through simulation programs constructed on MATLAB. It was found that the NFE cannot be eliminated but can be minimized and the number of folds contributed by pseudorandom binary sequence (PRBS) in MWC plays a vital role achieving that. Together with the detailed investigation carried out on the PRBS, it is proven that if the PRBS is modified, the NFE in MWC can be reduced. With that as the foundation, a concept was proposed and tested for the effectiveness. It was concluded that proposed concept is effective in reducing the NFE in MWC with an assumption that the received signals are similar.